PEMBELAJARAN MATEMATIKA MATERI SOAL CERITA DENGAN STRATEGI SCAFFOLING DI SEKOLAH DASAR - - Tumardi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2012)
Abstract: The purpose of this classroom action research was to describe a process of scaffolding and students' performance development in finishing story problem. The subjects of the research were third grade SDN (state elementary school) Sutojayan Pakisaji Malang. Analysis of the research used qualitative descriptive. This type of analysis emphasized on aspects of meaning towards events than quantitative data. The results of the research revealed students' performance in each of the zone of proximal development (ZPD) could be developed constitently. The development can be seen as effects  of: (1) instruction which gives students exhibit their actual performance, (2) Precision of students' actual  performance  identification by teachers, (3) Precision of directive questions and meaning' negotiation towards students performance, and (4) direct positive and negative reinforcement.   Abstrak: penelitian tindakan kelas ini bertujuan untuk mendeskripsikan proses scaffolding bagi perkembangan performansi siswa dalam menyelesaikan soal cerita. Subyek penelitian kelas III SDN Sutojayan Pakisaji Malang. Analisis data deskriptif kualitatif, lebih menekankan pada aspek makna suatu peristiwa daripada kuantitas data yang diperoleh. Hasil penelitian tentang strategi scaffolding menunjukkan performansi siswa pada setiap zone of proximal development (ZPD) dapat berkembang secara konsisten. Perkembangan itu diyakini sebagai akibat dari (1) pembelajaran yang menyediakan kesempatan siswa menunjukkan performansi aktualnya, (2) ketepatan pengidentifikasian performansi aktual siswa oleh guru, (3)ketepatan pertanyaan pengarah dan negosiasi makna atas performansi siswa, dan (4) pemberian penguatan positif mau pun negatif dengan segera.